Analysis of the impact of diagnostic virology tests on the use of antibiotics in paediatric inpatients with community-acquired pneumonia() - Aguilera-Alonso, David (Enfermedades infecciosas y microbiologia clinica (English ed.), 2020)
INTRODUCTION: Viruses are one of the most common causes of community-acquired pneumonia (CAP) in children. Early identification of respiratory viruses could result in a decrease in the use of antibiotics. METHODS: Observational, retrospective study from January 2014 to June 2018, that included paediatric patients admitted with a diagnosis of CAP in a tertiary hospital, in which antigenic tests and/or viral PCR on a respiratory sample was performed. RESULTS: A total of 105 CAP episodes were included, with identification of a respiratory virus in 93 (88.6%) cases. Patients with respiratory syncytial virus (RSV) detection had a lower onset of empirical antibiotic therapy (35.1% vs. 55.9%, p-value = .042). In addition, cases with RSV or influenza identification required shorter duration of antibiotic therapy (receiving 45.6% ≥2 days vs. 68.8% of those not identified, p = .017). CONCLUSION: The use of respiratory virus diagnostic techniques in our setting can optimise antibiotic use in children admitted with CAP.